KNOW AND MENTORING E-COMMERCE MARKET FOR MSMES IN LIALANG-SERANG VILLAGE: PENGENALAN DAN PENDAMPINGAN PEMANFAATAN MARKETPLACE E-COMMERCE BAGI PELAKU UMKM DI KELURAHAN LIALANG-SERANG - Isnaini Mahuda; Aria Cendana Kusuma; Ranny Meilisa (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Human physical movement space has increasingly limited the effects of the Covid-19 pandemic online businesses are increasingly mushrooming in the community. Nowadays, it is getting familiar term e-commerce which stands for electronic commerce, which means trading electronically. With this e-commerce many many berhingga-bagi existing, it can not be dipupong that e-commerce provides a good enough for angkatanni. Growing e-commerce is also inseparable from the name of the marketplace. One type of business that began to have many marketplaces is Micro, Small, and Medium Enterprises (MSMEs). Lialang village, located in Taktakan-Kota Serang Subdistrict, has many MSME umkm actors engaged in production, handicrafts, and many other productions. Which method is the way of community activities is training and mentoring that berkurun. This activity is the community in Keluarahan Lialang, especially UMKM actors subdistrict a lot of information and education about e-commerce and know various types of marketplaces, benefits and which ones become dilim online through the marketplace as well. In addition, this activity can be a business of MSMEs for their products broader existing marketplace and innovate and change in its more advanced and growing business